Study on sneak path effect in self-rectifying crossbar arrays based on emerging memristive devices - Chen, Ziang; Zhang, Guofu; Cai, Hao; Bengel, Christopher; Liu, Feng; Zhao, Xianyue; Kvatinsky, Shahar; Schmidt, Heidemarie; Waser, Rainer; Menzel, Stephan; Du, Nan (Frontiers in Electronic Materials, 2022)
The high demand for performance and energy efficiency poses significant challenges for computing systems in recent years. The memristor-based crossbar array architecture is enthusiastically regarded as a potential competitor to traditional solutions due to its low power consumption and fast switching speed. Especially by leveraging self-rectifying memristive devices, passive crossbar arrays potentially enable high memory densities. Nonetheless, due to the lack of a switching control per cell, these passive, self-rectifying memristive crossbar arrays (srMCA) suffer from sneak path current issues that limit the range of accurate operation of the crossbar array. In this work, the sneak path current issues in the passive srMCAs based on self-rectifying bipolar and complementary switching memristive devices are comparatively analyzed. Under consideration of the worst-case scenario, three reading schemes are investigated: one wordline pull-up (OneWLPU), all wordline pull-up (AllWLPU), and floating (FL) reading schemes. As a conclusion, despite different switching dynamics, both types of self-rectifying memristive devices can efficiently suppress sneak path current in the srMCAs. In the FL reading scheme, the sneak path current flowing through the unselected reversely biased memristive cells in the srMCA can be considered as an accurate estimation for the practical sneak path current in the srMCA. By analyzing the sneak path current in the srMCAs with a size up to 64 x 64, it is demonstrated that the leakage current plays a crucial role for suppressing the sneak path current, and the sneak path current via an individual cell exhibits a continuous decrease while the accumulated total sneak path current in the unselected reverse biased region is increasing with expanding the crossbar size. The comparative study on the bipolar and complementary memristive devices based srMCAs under diverse reading schemes reveals the influence of the switching dynamics on the sneak path current effect in the srMCAs, and provides a beneficial reference and feasible solutions for the future optimization of the crossbar topology with the intention of mitigating sneak path effects.